Epistolario de san Josemaría Escrivá de Balaguer y mons. Javier Lauzurica (enero 1934 – diciembre 1940) / Correspondence between St. Josemaría Escrivá and Msgr. Javier Lauzurica (January 1934 – December 1940) - Francisco Crosas (Studia et Documenta)
The letters between St. Josemaría Escrivá and Msgr. Javier Lauzurica are published in this study. The article presents the historical and human factors behind the correspondence maintained in a troubled period of the history of Spain.